Estrogen decreases TNF gene expression by blocking JNK activity and the resulting production of c-Jun and JunD - Srivastava, Sunil (American Society for Clinical Investigation, 1999)
Central to the bone-sparing effect of estrogen (E(2)) is its ability to block the monocytic production of the osteoclastogenic cytokine TNF-α (TNF). However, the mechanism by which E(2) downregulates TNF production is presently unknown. Transient transfection studies in HeLa cells, an E(2) receptor–negative line, suggest that E(2) inhibits TNF gene expression through an effect mediated by estrogen receptor β (ERβ). We also report that in RAW 264.7 cells, an E(2) receptor–positive murine monocytic line, E(2) downregulates cytokine-induced TNF gene expression by decreasing the activity of the Jun NH(2)-terminal kinase (JNK). The resulting diminished phosphorylation of c-Jun and JunD at their NH(2)-termini decreases the ability of these nuclear proteins to autostimulate the expression of the c-Jun and JunD genes, thus leading to lower production of c-Jun and JunD. The consequent decrease in the nuclear levels of c-Jun and JunD leads to diminished binding of c-Jun/c-Fos and JunD/c-Fos heterodimers to the AP-1 consensus sequence in the TNF promoter and, thus, to decreased transactivation of the TNF gene. J. Clin. Invest. 104:503-513 (1999).